ANALISIS SWOT TERHADAP PROSEDUR KLAIM ASURANSI PRODUK UNIT LINK (STUDI KASUS PADA PT ASURANSI JIWA SYARIAH BUMI PUTERA 1912) - Sri Bella Larasaty Yuandra; Nurbaiti; Nurul Jannah (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
This research is to find out the procedures for filing unit link insurance product claims at PT AJS Bumiputera Medan branch and to find out the SWOT analysis of submitting unit link product insurance claims PT AJS Bumiputera 1912 Medan branch. The formulation of the problem in this study is 1) What is the procedure for submitting unit link product insurance claims at PT AJS Bumiputera? 2) How is the SWOT analysis of the submission of unit link product claims at PT Asuransi Jiwa Syariah Bumiputera Medan Branch. This research uses qualitative methods, and the research approach used is direct research conducted by interviewing companies. In this study the authors used document research by collecting data and information through document archives. And using two data sources, namely primary data and secondary data. This research is that the results of a SWOT analysis of the insurance claim procedure for unit linked products. By using SO, WO, ST, and WT. The procedure provided by the company is very clear and makes it very easy for the insured. Claim procedures can make claims division easier, however, not all participants understand the applicable procedures. Settlement of claims for the company's decision-making process in collaboration with the police to facilitate the claims division with surveys to locations to find facts.